GENOTYPE VARIATION OF HEPATITIS C VIRUS IN DISTRICT BUNER SWAT - Mahmood, Khalid; Mohammad, Noor; Abidullah, Abidullah (Journal of Ayub Medical College Abbottabad, 2011)
Objective: To determine the frequency of various genotypes of Hepatitis C virus in District Buner, Swat. Methods: This Descriptive case series study was conducted at District Headquarter Hospital Daggar, and Bilal Medical Trust, Pir Baba, Swat, Pakistan from January 2007 to June 2008. A total of 400 patients, 154 Male and 246 Female aged 16-65 years (Mean age 31±13 years) without clinical and ultrasonographic evidence of cirrhosis, and with positive Hepatitis C Virus (HCV) antibodies by ELIZA, and HCV RNA detected by PCR were included. Hepatitis C virus genotypes were checked in serum by real time PCR (RT-PCR). Results: Genotype 3 was the most common type accounting for 61.5% of the study population. Amongst the subtypes, 182 (45.5%) had genotype 3a and 64 (16%) had genotype 3b. Thirty-five (8.7%) patients had genotype 1a, 12 (3%) had genotype 1b. Twenty-six (6.5%) patients had genotype 2a. Four (1%) patients had genotype 2b. Three (0.75%) patients had genotype 4a, and 1 (0.25%) had genotype 6a. Sixty-four (16%) patients had mixed infections. Forty (10%) patients had genotype 3a and 3b, 12 (3%) patients had genotype 1a, 1b, and 9 (2.25%) patients had genotype 2a and 1c, 2 (0.5%) had genotype1a, 3a and 1 patient (0.25%) had genotype1a, 3b. Nine (2.25%) patients had untypable genotype. Conclusion: Genotype 3 with its subtypes 3a and 3b is the commonest Hepatitis C virus present in District Buner, Swat. The others in order of decreasing frequency are genotype 1a, 2a and mixed types. Keywords: Hepatitis C virus, HCV, Genotypes, District Buner